Pengaruh Pelatihan dan Kreatifitas Usaha terhadap Pengembangan UMKM (Riset UMKM Sektor Ekonomi Biru di Kecamatan Mayangan, Kota Probolinggo) - Verto Septiandika; Nurul Jannah Lailatul Fitria (Jurusan Akuntansi Politeknik Negeri Pontianak, 2022)
UMKM greatly affects environmental conditions. The government several programs and policies the blue economy. UMKM actors need to receive training gradually and periodically. The training has an impact on increasing knowledge, business management capabilities, innovation, business networks and production. Creativity is needed in business development, in order to keep up with the times, technology, lifestyle, and others. This research has the aim of knowing the effect of training and entrepreneurial creativity on the development of MSMEs specifically processed fish and marine products in Mayangan District. This research applies quantitative methods with collection techniques through questionnaires. Data analysis technique applied is descriptive analysis and statistical analysis consisting of validity test, reliability test, classical assumption test, multiple linear regression test, hypothesis testing in the form of coefficient of determination test t test and F test. The results of this research prove that training affect UMKM Development (Y) by 2.913 and the Creativity variable affects UMKM Development by 2.244. In general, the variables of training and creativity have a positive influence on the development of SMEs in Mayangan District, Probolinggo City. The results of the test of the influence of the variable Training and Entrepreneurial Characteristics affect the development of UMKM of 6.94.